Consumer Behavior / Implications for Marketing Strategy - Best Roger J.; Coney Kenneth A; Hawkins Del I (Irwin Mcgraw-Hill, 1995)
Introduction, External Influences, Internal Influences, Consumer Decision Process, Organizations as Consumers, Consumer Behavior and Marketing Practice and Society, Index.
Introduction, External Influences, Internal Influences, Consumer Decision Process, Organizations as Consumers, Consumer Behavior and Marketing Practice and Society, Index.